The Mercury Resistance Operon: From an Origin in a Geothermal Environment to an Efficient Detoxification Machine - Boyd, Eric; Barkay, Tamar (Frontiers in Microbiology, 2012)
Mercuric mercury (Hg[II]) is a highly toxic and mobile element that is likely to have had a pronounced and adverse effect on biology since Earth’s oxygenation ∼2.4 billion years ago due to its high affinity for protein sulfhydryl groups, which upon binding destabilize protein structure and decrease enzyme activity, resulting in a decreased organismal fitness. The central enzyme in the microbial mercury detoxification system is the mercuric reductase (MerA) protein, which catalyzes the reduction of Hg(II) to volatile Hg(0). In addition to MerA, mer operons encode for proteins involved in regulation, Hg binding, and organomercury degradation. Mer-mediated approaches have had broad applications in the bioremediation of mercury-contaminated environments and industrial waste streams. Here, we examine the composition of 272 individual mer operons and quantitatively map the distribution of mer-encoded functions on both taxonomic SSU rRNA gene and MerA phylogenies. The results indicate an origin and early evolution of MerA among thermophilic bacteria and an overall increase in the complexity of mer operons through evolutionary time, suggesting continual gene recruitment and evolution leading to an improved efficiency and functional potential of the Mer detoxification system. Consistent with a positive relationship between the evolutionary history and topology of MerA and SSU rRNA gene phylogenies (Mantel R = 0.81, p < 0.01), the distribution of the majority of mer functions, when mapped on these phylograms, indicates an overall tendency to inherit mer-encoded functions through vertical descent. However, individual mer functions display evidence of a variable degree of vertical inheritance, with several genes exhibiting strong evidence for acquisition via lateral gene transfer and/or gene loss. Collectively, these data suggest that (i) mer has evolved from a simple system in geothermal environments to a widely distributed and more complex and efficient detoxification system, and (ii) merA is a suitable biomarker for examining the functional diversity of Hg detoxification and for predicting the composition of mer operons in natural environments.